Betamethasone Gel versus Intravenous Dexamethasone as Prophylaxis against Postoperative Sore Throat (Delta Medical College Journal, 2018)
Background: Postoperative sore throat (POST) though a minor sequel after general anaesthesia with endotracheal intubation, it can be distressing to the patient.Objective: The effectiveness of lubricating endotracheal tube with 0.05% betamethasone gel or intravenous dexamethasone in reducing the postoperative sore throat was compared.Materials and method: This was a prospective study carried out among ninety ASA I and II informed consenting patients aged 20-50 years undergoing elective surgery under general anaesthesia with endotracheal intubation. The patients were randomly divided into three groups with thirty subjects in each group. Betamethasone gel (0.05%) was applied over endotracheal tube over 15 cm mark from the tip in group I, intravenous dexamethasone was given in group II and group III was taken as control. In post-anaesthesia care unit, an anesthesiologist interviewed all patients on postoperative sore throat at 1 hour, 6 hours and 24 hours after operation.Results: At 24 hours following extubation, there was statistically significant lower incidence of post-operative sore throat (POST) in betamethasone group compared to other two groups (betamethasone group 3.33%, dexamethasone group 20% and control group 26.66%, p